Diagnosis of cervical - Lymph adenopathyAccording to age groups (Tikrit Journal of Pharmaceutical Sciences, 2023)
Cervical — Lymphadenopathy is common problem , both in children and adults. Aim of study . to determine the most professional — dinguosis ul cervical — Lymphadenopathy according to patient age . over period Lasting from Jan - 2007 to Nov . 2009 , prospective study of ( 83) patients from ( both sexes ), ( male : 51 ){ Female : 32) with cervical — Lymphadenopathy were taken and divided into two age groups ( pediatric age group < Sy ) and ( Adult age group 16-72 y) . Diagnosis of cervical —Lymphadenopathy depend on clinical — examination , radiological — examination , FNA(Fine Needle Aspiration) , and in some cases excisional biopsy was taken. Result :this study showed that inflammatory and infectious diseases had the highest incidence in pediatric age group ( 65.7%) of total pediatric cases , followed by primary malignant cervical — Lymphadcnopathy ( 25.7% ) , the lowest was the secondary imelasteses (8.6% )- while in adult age group secondary cervical Lymphedenopathy (metastases) was the commonest ( 41.71 ) Followed by infectious and inflammatory Lesion ( 37.51) , the Lowest was the primary ervival — Lymphadenopathy (20.8%) Conclusion : In this smudy infectious and inflammatory cervical — lymphadenopathy was the commonest in pediatric age group , while secondary cervical lymphadenopathy —( metasteses) was the commonest in adult age group .